EFFECT OF ORGANIC NPK FERTILIZER AND HANTU PLANT GROWTH REGULATOR (PGR) APPLICATION ON GROWTH AND YIELD OF CELERY (Apium graveolus L.) - Indra Kurniawan; Elfin Efendi; Deddy Wahyudin Purba (Bernas : Jurnal Penelitian Pertanian, 2018)
This research was conducted on Durian street, Kisaran Timur, Asahan Regency of North Sumatera Province with flat topography and is at an altitude of 15 m above sea level. The study was conducted from March to May 2017. This research was arranged based on Factorial Randomized Block Design with 2 treatment factors and 3 replications. The first factor is organic NPK with 3 levels: N0 = 0 g/plot, N1 = 25 g/plot, N2 = 50 g/plot. Second factor with PGR Hantuwith 4 levels ie Z0 = 0 ml/l water, Z1 = 1 ml/l water, Z2 = 2 ml/l water, and Z3 = 3 ml/l water. The results showed that organic NPK fertilizer was the best treatment that produced 32,34 cm height, 21,58 pieces of leaves, 65,53 g per plant and 1.75 kg per plot production. The best treatment of PGR Hantu was obtained at a dose of 2 ml/l of water yielding a plant height of 30.99 cm, thenumber of leaves was 21.86 pieces, the production per plant was 67.15 g and the production per plot was 1.78 kg. The interaction between organic NPK fertilizer and PGR Hantu had no significant effect on all observed variables.